Sarcoidosis subcutánea sin compromiso sistémico - Moya G., Nicolás; Araya B., Irene; Zemelman D., Viviana; Carreño T., Laura (Revista Hospital Clínico Universidad de Chile, 2017)
We present the case of a 52 year old woman with a history of bilateral ovarian cancer operated. The patient attended the dermatology unit for a sudden onset of a left plantar nodule of three weeks of evolution, painful on walking, with no other history in particular. At physical examination, the patient presented a surface nodule slightly hyperpigmented, with ill-defined edges, round shape, firm consistency, mobile and painful to compression, one cm of diameter, in the middle third of the left plant. No concomitant scars are seen. Doppler soft tissue ultrasound is requested, showing a granulomatous nodule on the surface of the plantar aponeurosis. The biopsy lesion revealed non-caseating granulomas in cell tissue, PAS and Ziehl-Neelsen staining are negative A left plantar subcutaneous sarcoidosis is diagnosed, systemic involvement is ruled out. Within the first year of follow-up, there are no new lesions or findings compatible with systemic disease.